Recuperação de interfaces preferenciais em materiais monofásicos por análise de reflexões proibidas em difração de raios-X síncroton - Lorena Aarão Rodrigues (2019)
The development and performance of materials is intrinsically related to our capability of understanding thermal treatments, mechanical processing and chemical alloying down to the nanoscale. In this sense, unraveling the structure of interfaces is crucial for the opening of new regimes in property-performance space for a given material system. Interface arrangements have been mainly characterized by imaging techniques such as scanning and transmission electron microscopy, which can access structural data locally, but are destructive and statistically limited. In this work, a large angular range detector covering up 120° of scattering angle was used to accumulate counts from synchrotron X-ray diffraction measurements on commercially pure Mg samples. Long acquisition times allowed the retrieval of preferential interface structure configurations through the observation of very weak diffraction peaks. Additional peaks were located close to fundamental reflections. A kinematical simulation scanning possible interface structures was carried out to establish the correspondence of non-bulk peaks with the interfacial structural organization of atoms which may be responsible for such scatterings. The simulated interfaces were probed for a wide range of angular displacements with respect to the main cleavage planes of the bulk system. The information retrieved about the maximum strain at the interface plane (with respect to a pure bulk configuration) and their geometry are related with conditions that lead to local energy minimization with a symmetry that allows for the observation of x-ray diffraction, representing a long-range ordered pattern of atomic distributions in Mg. The introduced methodology allows for non-destructive monitoring changes in a system when it undergoes mechanical processes that may, for instance, modify grain sizes and orientation.